Local Democracy Challenges: Vote Buying and Elite Patronage in the 2024 North Gorontalo Election - Santoso, Eka Putra B; Fata, Ahmad Khoirul; Dian Adi Perdana (JURNAL TAPIS, 2026)
This study analyzes the practices of money politics, patronage, and disputes over election results that led to a revote (PSU) in the dynamics of the regional elections in North Gorontalo Regency. It aims to explain how the relationships among political elites, business actors, and local networks shape voting behavior and influence the quality of local democracy. Employing a qualitative-analytical literature approach, this research analyzes official documents, Constitutional Court rulings, election supervisory reports, and relevant theories on vote buying and political clientelism. The findings reveal that the re-voting process did not necessarily improve democratic quality; instead, it increased political costs and strengthened candidates’ dependence on financial sponsors. Vote buying operated through patron–client mechanisms mediated by village officials and local brokers, making such practices difficult to prove within formal legal frameworks. Moreover, the legalistic interpretation of structured, systematic, and massive (TSM) violations allowed many substantive infractions to escape sanctions. These conditions indicate that local democracy remains largely procedural and tends toward oligarchic tendencies. Without reforms in political financing and stronger party institutionalization, local elections risk reproducing elite dominance rather than popular sovereignty.